EXAMINING THE UNEVEN DISTRIBUTION OF HOUSEHOLD TRAVEL CARBON EMISSIONS WITHIN AND ACROSS NEIGHBORHOODS: THE CASE OF BEIJING. (16th May 2016) - Xiao, Zuopeng; Lenzer, James H.; Chai, Yanwei
ABSTRACT: Although a growing number of studies have scrutinized population‐based variations in travel carbon emissions, few have examined these variations and uneven composition at the neighborhood level. Based on a 2007 Beijing household daily travel/activity survey, this paper attempts to calculate household daily travel carbon emissions and delineate the heterogeneous distribution within and across different neighborhoods. Using multilevel regression models, this paper confirms that socioeconomic variables (especially car availability) are the dominant contributing factors to household travel carbon emissions. Increasing the population density, land use mix and access to metro stations decreases emissions; whereas, household travel emissions increase along with the residential distance to the city center. Moreover, these effects vary across neighborhoods. Consequently, besides behavioral change policies aimed at high emitters, land use instruments should be targeted to different neighborhoods. The observed heterogeneous distributions call for a new governance framework to develop more effective and equitable urban transport policies.